Given a - b = 2, a3 - b3 = 26, then (a + b)2 is?

  • 19
  • 24
  • 316
  • 412
Answer:- 1
Explanation:-

Solution:
ab=2 a3b3=26a3b3=(ab)(a2+ab+b2)26=(2)(a2+ab+b2)13=(a2+ab+b2)....(i)4=13+ab(ab)2=a2+b22ab(2)2=a2+b2+ab3ab3ab=9ab=3(a+b)2=(ab)2+4ab=4+4×3=16

Post your Comments

Your comments will be displayed only after manual approval.

", "dateCreated": "7/24/2019 10:09:12 AM", "author": { "@type": "Person", "name": "Nitin Sir" } }, "suggestedAnswer": { "@type": "Answer", "text": "
Solution:
ab=2 a3b3=26a3b3=(ab)(a2+ab+b2)26=(2)(a2+ab+b2)13=(a2+ab+b2)....(i)4=13+ab(ab)2=a2+b22ab(2)2=a2+b2+ab3ab3ab=9ab=3(a+b)2=(ab)2+4ab=4+4×3=16
", "dateCreated": "7/24/2019 10:09:12 AM" } }
Test
Classes
E-Book